PENERAPAN SISTEM AKUNTANSI PADA PT LAPAK NIAGA GROUP - O Feriyanto; Syahrul ramdani; M deva fadilah; Putri asiyah; Iis rahmawati (Jurnal Publikasi Manajemen Informatika, 2024)
The accounting information system in the accounting cycle stages is part of the overall accounting information system designed and implemented by the company. An effective accounting information system is also very important for the long-term success of a company. PT. Lapak Niaga Group is a company that operates in the manufacturing sector, namely producing curtains, bed sheets and bed covers. Judging from its business activities, PT. Lapak Niaga Group is a complex business entity so it requires a good accounting information system to support its activities. The purpose of this research is to find out how best to implement the Accounting Information System in the accounting cycle at PT. Lapak Niaga Group runs according to correct procedures. The research approach used in this research is qualitative, with the scope covering PT. Lapak Niaga Group as the object and subject of research are the parts involved in the company's accounting system. The unit of analysis in this research is the implementer of the income accounting system at PT. group trading stall. From this research it can be concluded that the application of the Accounting Information System in the Revenue cycle at PT. Lapak Niaga Group is not yet fully capable. This can be seen from the fact that there are still multiple roles played by several functions in the organization. The most striking dual role is in the accounting department where in the company the cashier functions as cash receiver, recorder and report preparer.